2014
DOI: 10.1364/boe.5.003150
|View full text |Cite
|
Sign up to set email alerts
|

Dual modality optical coherence and whole-body photoacoustic tomography imaging of chick embryos in multiple development stages

Abstract: Abstract:Chick embryos are an important animal model for biomedical studies. The visualization of chick embryos, however, is limited mostly to postmortem sectional imaging methods. In this work, we present a dual modality optical imaging system that combines swept-source optical coherence tomography and whole-body photoacoustic tomography, and apply it to image chick embryos at three different development stages. The explanted chick embryos were imaged in toto with complementary contrast from both optical scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…This was not achieved by previous three-dimensional (3D) technologies such as optical coherence tomography and photoacoustic tomography (Wong et al, 2013;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…This was not achieved by previous three-dimensional (3D) technologies such as optical coherence tomography and photoacoustic tomography (Wong et al, 2013;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…1(b) (Solid Edge ST6, Siemens Industry Software GmbH, Germany). Compared to other all optical PAT/OCT systems' configurations [16,18], this newly designed probe has all degrees of freedom to be positioned pertaining to the regions being imaged. The switchable sensor holder slides in and out of the slot easily, permitting fast removing and changing of sensor holder to allow OCT a clear scanning window without FPI.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of using piezoelectric detectors for PAT, all optical PAT has been demonstrated to achieve satisfactory results when combined with either spectral domain OCT (SD-OCT) or swept source OCT (SS-OCT) [17]. Both preclinical results for in toto chick embryo imaging [18] and clinical skin disease imaging [16] have been shown, proving its usefulness in biomedical imaging. So far, however, in these dual modality PAT/OCT systems, the OCT part is only used to provide 1 to 2 mm of scattering based surface structural detail.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1(a) shows the schematic of the multimodal system. Descriptions of the sweptsource OCT and the excitation setups were given in detail in our previous publication [21] and the PAT interrogation in [18]. For this study the benchtop scan unit used in the previous system was redesigned and modified into a new imaging head whose footprint is 540 cm 2 (84 in 2 ) and is independent of the optical table, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [20] used the combined PAT/OCT to image a healthy human subject with the images of the submodalities inherently coregistered. Liu et al [21] with a similar combined PAT/OCT system provided complementary information with clinical relevance from imaging a chick embryo ex ovo. A recent review article [7] has shown several different types of PAM/OCT systems.…”
Section: Introductionmentioning
confidence: 99%